Design of an Electronically Adaptable Low-power Reference Cell for Low-cost CMOS Processes - Heidrich, Jürgen; Brenk, Daniel; Essel, Jochen; Heinrich, Matthias; Hofer, Günter; Holweg, Gerald; Weigel, Robert; Fischer, Georg (18th International Conference on Microwave Radar and Wireless Communications (MIKON), 2010)
This paper presents the design of a voltage reference cell suitable for low-voltage and low-power applications without the usage of bipolar structures. The respective reference voltage can be trimmed within a certain range to compensate the unavoidable process variations. The chip is designed based on a 0.13 μm CMOS technology.
elib2cris::1512001600,heidrich2010c
Keywords: CMOS technology; circuits; Photonic band gap; Joining processes; Temperature dependence; Threshold voltage; CMOS; RFID; bias cell; low-power; low-voltage; reference circuit; reference voltage; wireless sensing